Morchella steppicola Zer.: морфологічні особливості, ультраструктура та поширення в Південно-Східній Україні - Сухомлин, М.М.; Куткова, О.В.; Паніна, З.О. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
Указаны новые места распространения Morchella steppicola Zer. в Юго-Восточной Украине: 15 — в Донецкой обл., 2 — в Луганской и 1 — в Запорожской. Описаны места плодоношения. Впервые с помощью сканирующего электронного микроскопа исследованы особенности макроморфологии плодовых тел и ультраструктуры асков, парафиз и аскоспор. In the article new places of distribution Morchella steppicola Zer. in the South-East part of Ukraine are indicated. 15 points of a growth of the given species in Donetsk region, 2 points in Lugansk and 1 — in the Zaporozhye region are marked. Places of fructification of a M. steppicola are described. For the first time with the help of a scanning electron microscopy peculiarities of macromorphol-ogy of fruit bodies and ultrastructures of ascus, paraphysises and ascospores of M. steppicola are investigated.